2014
DOI: 10.4028/www.scientific.net/amm.575.231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca Addition on Chemical Composition, Microstructure and Dielectric Properties of BaTiO<sub>3</sub>

Abstract: Owing to its high dielectric constant, barium titanate is a material commonly employed in fabrication of high energy density capacitors. Dielectric properties required for practical applications can be attained in barium titanate with desired chemical composition and microstructure. This study, therefore, aims at examining effects of additive contents on formation of secondary phases, microstructure and dielectric properties of BaTiO3 and BaTiO3 with 20-40 at% Ca. Chemical composition analysis revealed that si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[64][65] When the grain size of BaTiO3 particles further decreases to micron level, the relative dielectric constant firstly increases and then decreases. [66] In Figure 6, it is observed that with the decrease of grain size, the dielectric constant of BaTiO3 particles decreases remarkably. The reason is that with the decrease of grain size, the fraction of cubic layer on particle surface increases, resulting in the decrease of tetragonal phase and ferroelectricity of BaTiO3 particles.…”
Section: Effect Of Grain Size On Dielectric Constantmentioning
confidence: 93%
“…[64][65] When the grain size of BaTiO3 particles further decreases to micron level, the relative dielectric constant firstly increases and then decreases. [66] In Figure 6, it is observed that with the decrease of grain size, the dielectric constant of BaTiO3 particles decreases remarkably. The reason is that with the decrease of grain size, the fraction of cubic layer on particle surface increases, resulting in the decrease of tetragonal phase and ferroelectricity of BaTiO3 particles.…”
Section: Effect Of Grain Size On Dielectric Constantmentioning
confidence: 93%